Socio-Legal Approaches To Combat Fake News (Hoax) On Social Media Pertaining Covid-19 In Batam City (A Case Study Of The Virginia Ship) - Situmeang, Ampuan; Shahriyani Shahrullah, Rina; Brelly, Adolfh (Universitas Ekasakti, 2023)
In 2020, a hoax was disseminated through social media in Batam City, claiming that the captain of the Virginia Ship had contracted Covid-19. This hoax immediately caused significant concern among the residents of Batam City, as the ship was anchored in their city. This study aims to identify the strategies employed by the Regional Police of Riau Islands Province to combat hoaxes, specifically focusing on the case of the Virginia Ship. To achieve this objective, socio-legal research was conducted, which involved in-depth interviews with relevant stakeholders from the Regional Police of Riau Islands Province. Additionally, secondary data collected through library research was utilized. All data was qualitatively analyzed. The findings of the study indicate that the enforcement of laws against hoaxes on social media pertaining to COVID-19 news in Batam City has been effective. This success can be attributed to the establishment of a Cyber Crime Investigation Satellite Office situated at the Kepulauan Riau Regional Police headquarters.